Perceptual analysis of directional late reverberation - Alary, Benoit; Massé, Pierre; Schlecht, Sebastian J.; Noisternig, Markus; Välimäki, Vesa (Journal of the Acoustical Society of America, 2021)
The late reverberation characteristics of a sound field are often assumed to be perceptually isotropic, meaning that the decay of energy is perceived as equivalent in every direction. In this paper, we employ Ambisonics reproduction methods to reassess how a decaying sound field is analyzed and characterized and our capacity to hear directional characteristics within late reverberation. We propose the use of objective measures to assess the anisotropy characteristics of a decaying sound field. The energy-decay deviation is defined as the difference of the direction-dependent decay from the average decay. A perceptual study demonstrates a positive link between the range of these energy deviations and their audibility. These results suggest that accurate sound reproduction should account for directional properties throughout the decay.
CRIS-Team Scopus Importer:2023-11-06